Complex relationship between growth hormone and sleep in children: insights, discrepancies, and implications - Zaffanello, Marco; Pietrobelli, Angelo; Cavarzere, Paolo; Guzzo, Alessandra; Antoniazzi, Franco (Frontiers in Endocrinology, 2024)
Growth hormone (GH) is crucial to growth and development. GH secretion is regulated by a complex feedback system involving the pituitary gland, hypothalamus, and other organs, and predominantly occurs during deep sleep. Isolated and idiopathic growth hormone deficiency (GHD) is a condition characterized by GHD without any other signs or symptoms associated with a specific syndrome or disease. The aim of this narrative review was to evaluate the relationship between GH and sleep in children using published data. Various databases (Medline/PubMed, Scopus, and Web of Science) were systematically searched for relevant English language articles published up to April 2023. Search strategies included the terms ‘children/pediatric’, ‘growth hormone’, ‘growth hormone deficiency’ and ‘sleep’. Data were extracted by two independent reviewers; 185 papers were identified of which 58 were duplicates and 118 were excluded (unrelated n=83, syndromic/genetic GHD n=17, non-English n=13, abstract n=1, case report n=1). Overall, nine studies (six clinical studies, two case series, and one survey) were included. GHD appears to have an adverse effect on sleep in children, and GH therapy has only been shown to have a beneficial effect on sleep parameters in some individuals. Notably, identified data were limited, old/poor quality, and heterogenous/inconsistent. Further research of GHD in pediatric populations is necessary to improve the understanding of GHD impact on sleep and its underlying mechanisms, and to determine the specific impacts of GH therapy on sleep in children.